Pterostichus (Cryobius) kurosawai Tanaka 1958 - Sundukov, Yurii N.; Novomodnyi, Evgeniy V. (Zenodo, 2022)
Pterostichus ( Cryobius ) kurosawai Tanaka, 1958 Material. Verkhne-Bureinskii Distr., upper reaches of the Umalta River, Dedovich’s hut, 13.07.2003, E. Novomodnyi leg., 1♂. Distribution. A subboreal East Asian species: the Russian Far East (the mountains of North Amur River Region, the Sikhote Alin, entire Sakhalin, the Shantar Islands), Japan (Hokkaido, Rishiri Island). Published as part of Sundukov, Yurii N. & Novomodnyi, Evgeniy V., 2022, Ground beetles (Coleoptera, Carabidae) of Khabarovsky Region in the collection of Grodekov Khabarovsk Regional Museum, pp. 570-593 in Amurian Zoological Journal XIV (4) on page 580, DOI:10.33910/2686-9519-2022-14-4-570-593, http://zenodo.org/record/12815734